Lateral Nasal Artery Perforator Flap for Nasal Reconstruction: Clinical Applications and Risk Factors Associated With Nasal Deformities. Issue 2 (February 2022) - Abe, Yoshiro; Ishida, Soushi; Mineda, Kazuhide; Yamashita, Yutaro; Nagasaka, Shinji; Yamasaki, Hiroyuki; Hashimoto, Ichiro
Abstract : Background: Nasal reconstruction is challenging because of the difficulty in balancing superior aesthetic outcomes and less invasive surgery. The use of the lateral nasal artery (LNA) perforator flap has been reported for nasal reconstruction. However, few reports have described appropriate applications of nasal reconstruction and assessments of nasal deformity. This study aimed to quantify the aesthetic outcomes on using this flap and reveal the risk factors associated with nasal deformities. Methods: Twenty patients underwent nasal reconstruction using the LNA flap with a cranial perforator adjacent to the nasal defect. Postoperative protuberant deformities were scored by 2 independent plastic surgeons using a 5-point Likert scale and classified as excellent, good, or poor. The risk factors of deformities were identified using univariate analyses. A nasal alar deviation index was developed to analyze correlations with flap harvesting. The sensory function was assessed by the Semmes-Weinstein test. Results: Flaps survived in 19 patients (95%), and 1 flap showed distal necrosis. All arterial perforators used remained within 5 mm lateral to the boundary between the cheek and nasal ala. The flaps were most often used to cover 2 subunits, including the nasal sidewall defects. Protuberant deformities in 6 (30%), 8 (40%), and 6 (30%) patients were classified as excellent, good, and poor, respectively. Nasal defects involving more than 3 subunits caused severe protuberant deformity. Only 2 patients (5%) in the good and fair groups underwent additional debulking surgery. Nasal alar deviation was not significantly correlated with flap harvesting, when the nasal alar deviation index before and after surgery were compared. Sensory function was retained in all patients. Conclusions: Aesthetic outcomes and sensory function were good on using the LNA perforator flap as a propeller flap having a wide arc of rotation. This flap is suitable for nasal reconstruction involving less than 2 nasal subunits without any severe nasal alar deviation deformity. In addition, this flap allows for better outcomes because it requires less invasive 1-stage surgery.